Value and effectiveness of National Immunization Technical Advisory Groups in low- and middle-income countries: a qualitative study of global and national perspectives. Issue 4 (10th May 2019) - Bell, Sadie; Blanchard, Laurence; Walls, Helen; Mounier-Jack, Sandra; Howard, Natasha
Abstract: The Global Vaccine Action Plan proposes that every country establish or have access to a National Immunization Technical Advisory Group (NITAG) by 2020. The NITAG role is to produce evidence-informed recommendations that incorporate local context, to guide national immunization policies and practice. This study aimed to explore the value and effectiveness of NITAGs in low- and middle-income countries (LMICs), identifying areas in which NITAGs may require further support to improve their functionality and potential barriers to global investment. A multi-methods study design was used, comprising 134 semi-structured interviews and 82 literature review sources that included 38 countries. Interviews were conducted with 53 global/regional and 81 country-level participants able to provide insight into NITAG effectiveness, including NITAG members, national immunization programme staff, and global agency representatives (e.g. the World Health Organisation, the Bill and Melinda Gates Foundation, Gavi the Vaccine Alliance). The review, including published and unpublished sources on NITAGs in LMICs, was conducted to supplement and corroborate interview findings. Data were analysed thematically. NITAGs were described as valuable in promoting evidence-informed vaccination decision-making, with NITAG involvement enhancing national immunization programme strength and sustainability. Challenges to NITAG effectiveness included: (1) unreliable funding; (2) insufficient diversity of member expertise; (3) inadequate conflicts of interest management procedures; (4) insufficient capacity to access and use evidence; (5) lack of transparency; and (6) limited integration with national decision-making processes that reduced the recognition and incorporation of NITAG recommendations. LMIC NITAGs have developed significantly in the past decade. Well-functioning NITAGs were trusted national resources that enhanced country ownership of immunization provision. However, many LMIC NITAGs require additional technical and funding support to strengthen quality and effectiveness, while maintaining impartiality and ensuring sufficient integration with national decision-making processes. Barriers to sustainable global support need to be addressed for LMIC NITAGs to both continue and develop further.